Interdependence of Gold Prices and Macroeconomic Variables Using A Vector Autoregression (VAR) Approach - Sri Sukma Wahyuni; Naswatun Zikra; Fakhruddin Fakhruddin; Cut Zakia Rizki; Nur Aidar; Thanawit Bunsit (Hasanuddin Economics and Business Review, 2026)
This study examines the dynamic interdependence between gold prices and selected macroeconomic variables in Indonesia, namely inflation, exchange rates, and interest rates, using a Vector Autoregression (VAR) approach. The study uses annual time-series data from 1990 to 2024. The empirical procedure includes the Augmented Dickey-Fuller unit root test, optimal lag length selection, VAR stability test, Granger causality test, Johansen cointegration test, Impulse Response Function, and Forecast Error Variance Decomposition. The VAR model is estimated using stationary first-differenced variables because no long-run cointegration relationship is detected among the variables. The results show that the relationships among gold prices, inflation, exchange rates, and interest rates are partial and mostly unidirectional. Exchange rates significantly influence inflation and interest rates, while inflation significantly influences interest rates. However, domestic macroeconomic variables have relatively weak direct effects on gold prices in the short run. Gold price fluctuations are primarily explained by their own innovations, although interest rate shocks generate a negative response in gold prices, supporting the opportunity cost channel. This study provides updated evidence on gold price dynamics in Indonesia and shows that gold prices are embedded in an asymmetric macroeconomic transmission system. The findings offer implications for investors, policymakers, and financial institutions in understanding gold as a partial hedging asset in an emerging market context.